Green Marketing and Sustainable Development Challenges and Opportunities: - (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In the modern era of globalization, it has become achallenge to keep the customers as well as consumers in fold and even keep ournatural environment safe and that is the biggest need of the time. Consumersare also aware of the environmental issues like; global warming and the impactof environmental pollution. Green marketing is a phenomenon which has developedparticular important in the modern market and has emerged as an importantconcept in India as in other parts of the developing and developed world, andis seen as an important strategy of facilitating sustainable development. Inthis research paper, main emphasis has been made of concept, need andimportance of green marketing. Data has to be collected from multiple sourcesof evidence, in addition to books, journals, websites, and newspapers. Itexplores the main issues in adoption of green marketing practices. The paperdescribes the current Scenario of Indian market and explores the challenges andopportunities businesses have with green marketing. Why companies are adoptingit and future of green marketing and concludes that green marketing issomething that will continuously grow in both practice and demand.